Protein turnover, amino acid requirements and recommendations for athletes and active populations - Poortmans,J.R. (2012)
Skeletal muscle is the major deposit of protein molecules. As for any cell or tissue, total muscle protein reflects a dynamic turnover between net protein synthesis and degradation. Noninvasive and invasive techniques have been applied to determine amino acid catabolism and muscle protein building at rest, during exercise and during the recovery period after a single experiment or training sessions. Stable isotopic tracers (13C-lysine, 15N-glycine, ²H5-phenylalanine) and arteriovenous differences have been used in studies of skeletal muscle and collagen tissues under resting and exercise conditions. There are different fractional synthesis rates in skeletal muscle and tendon tissues, but there is no major difference between collagen and myofibrillar protein synthesis. Strenuous exercise provokes increased proteolysis and decreased protein synthesis, the opposite occurring during the recovery period. Individuals who exercise respond differently when resistance and endurance types of contractions are compared. Endurance exercise induces a greater oxidative capacity (enzymes) compared to resistance exercise, which induces fiber hypertrophy (myofibrils). Nitrogen balance (difference between protein intake and protein degradation) for athletes is usually balanced when the intake of protein reaches 1.2 g·kg-1·day-1 compared to 0.8 g·kg-1·day-1 in resting individuals. Muscular activities promote a cascade of signals leading to the stimulation of eukaryotic initiation of myofibrillar protein synthesis. As suggested in several publications, a bolus of 15-20 g protein (from skimmed milk or whey proteins) and carbohydrate (± 30 g maltodextrine) drinks is needed immediately after stopping exercise to stimulate muscle protein and tendon collagen turnover within 1 h.